Dentoalveolar outcomes in maxillary reconstruction: A retrospective review of 85 maxillectomy reconstructions. Issue 7 (14th June 2021) - Petrides, George A.; Hicks, Gabrielle; Dunn, Masako; Froggatt, Catriona; Wallace, Christine; Howes, Dale; Leinkram, David; Low, Tsu‐Hui (Hubert); Ch'ng, Sydney; Wykes, James; Palme, Carsten E.; Clark, Jonathan R.
Abstract: Background: Although microvascular free flaps are often used to reconstruct maxillary defects, dentoalveolar rehabilitation is arguably less common despite its importance to midface function and aesthetics. The aim of this study is to review the contemporary management of maxillary defects in a single quaternary referral institution to identify factors that assist or impede dentoalveolar rehabilitation. Methods: A retrospective review of maxillary reconstructions performed between February 2017 and December 2020 was performed. Patient characteristics, defect classification, operative techniques, complications and dentoalveolar outcomes were recorded. Results: A total of 85 maxillary reconstructions were performed in 73 patients. Of the 64 patients where dental rehabilitation was required, 31 received a functional denture (48%) with 24 (38%) being implant‐retained. Significant predictors of successful rehabilitation included the use of virtual surgical planning (VSP; 86% vs. 25%, p  < 0.001), preoperative prosthodontic assessment (82% vs. 21%, p  < 0.001), prefabrication (100% vs. 40%, p  = 0.002) and use of the zygomatic implant perforator flap technique (100% vs. 39%, p  = 0.001). Preoperative prosthodontic consultation was associated with 21‐fold increase in the odds of rehabilitation (odds ratio 20.9, 95% confidence interval 6.54–66.66, p  < 0.005). Conclusion: Preoperative prosthodontic evaluation, VSP and reconstructive techniques developed to facilitate implant placement are associated with increased dental rehabilitation rates. Despite using an institutional algorithm, functional dentures are frequently prevented by factors including soft tissue constraints, disease recurrence and patient motivation. Abstract : Dentoalveolar rehabilitation following maxillary reconstruction is important to midface function and aesthetics. A review of 85 maxillary reconstructions was performed to identify factors that assist or impede dentoalveolar rehabilitation. Preoperative prosthodontic evaluation, virtual surgical planning and reconstructive techniques developed to facilitate implant placement were associated with increased dental rehabilitation rates. Despite using an institutional algorithm, functional dentures are frequently prevented by factors including soft tissue constraints, disease recurrence and patient motivation.